2019
DOI: 10.1002/esp.4614
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of salt marsh margins are related to their three‐dimensional functional form

Abstract: The three‐dimensional configuration of sedimentary landforms in intertidal environments represents a major control on regional hydrodynamics. It modulates the location and magnitude of forces exerted by tidal currents and waves on the landform itself and on engineered infrastructure such as sea walls or coastal defences. Furthermore, the effect is reflexive, with the landforms representing an integrated, long‐term response to the forces exerted on them. There is a strong reciprocal linkage between form and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 42 publications
3
18
0
Order By: Relevance
“…From a morphological point of view, self organization results in a jagged boundary profile when the marsh is subject to low wave energy and a uniform and smooth marsh boundary in case of high wave energy and high average erosion rates. It has thus been suggested that the shape of the marsh boundary could be used as a tool to evaluate the state of vulnerability of salt marshes under erosion (Leonardi & Fagherazzi, 2015; Leonardi, Defne, et al, 2016; Evans et al, 2019).…”
Section: Lateral Erosion and Progradation Of Salt Marshesmentioning
confidence: 99%
“…From a morphological point of view, self organization results in a jagged boundary profile when the marsh is subject to low wave energy and a uniform and smooth marsh boundary in case of high wave energy and high average erosion rates. It has thus been suggested that the shape of the marsh boundary could be used as a tool to evaluate the state of vulnerability of salt marshes under erosion (Leonardi & Fagherazzi, 2015; Leonardi, Defne, et al, 2016; Evans et al, 2019).…”
Section: Lateral Erosion and Progradation Of Salt Marshesmentioning
confidence: 99%
“…Given identical forcing conditions, the evolution of the marsh over longer (annual to decadal) timescales is thus not merely a function of substrate properties of the marsh and those exposed at the cliff, but also of those of the fronting tidal flat (Mariotti and Fagherazzi, 2010). Evans et al (2019) provide evidence for the importance of morphodynamic feedbacks in driving salt marsh morphological change through time. Edge erosion can, for example, inhibit further marsh loss when eroded material is deposited on the tidal flat, lowering the water depth and reducing wave power at the vegetated margin (Bendoni et al, 2016;Mariotti and Canestrelli, 2017).…”
Section: Role Of Substrate Properties In Salt Marsh Morphodynamicsmentioning
confidence: 94%
“…As the unprocessed point clouds were not supplied, a direct evaluation of the vertical accuracy could not be undertaken. Notice that accuracy depends on the Lidar sensor resolution (Wehr and Lohr, 1999), the landscape features of the intertidal environment (Evans et al, 2019) and the presence of vegetation (Hladik and Alber, 2012). In low and high marshes, the vegetation clearly influences the accuracy, causing errors from 0.1 to 0.45 m (Morris et al, 2005;Rosso et al, 2006;Wang et al, 2009;Schmid et al, 2011;Millard et al, 2013), requiring corrections to DTMs.…”
Section: Morphological Analysismentioning
confidence: 99%